Global hunger index of India based on National family health survey-IV with special reference to some states and critical review - Khobragade, Ashish Wasudeo; Rajan, K. (International Journal Of Community Medicine And Public Health, 2017)
Background: India is facing serious hunger situation now. Factors responsible for this hunger situation are different. This study focuses on hunger situation in 4 different states of India and remedial measures. Methods: Secondary data was collected from National Family Health Survey-IV (NFHS). Data entry was done in excel sheet. GHI was calculated using new formula given by IFPRI. Results: There are wide disparities in hunger situation in Indian states. Madhya Pradesh is in alarming state of hunger. Conclusions: Hunger situation in Indian states varies from states to states. Different types of interventions are required at each state level to improve the overall hunger situation.